Lighting for work: A study of the relationships among discomfort glare, physiological responses and visual performance. (January 2020) - Hamedani, Zahra; Solgi, Ebrahim; Hine, Trevor; Skates, Henry; Isoardi, Gillian; Fernando, Ruwan
Abstract: Objective measures of visual discomfort have the potential to quantify the individual's sensations under discomfort glare conditions although such measures have yet to be circumscribed. The present study aimed to examine the extent to which visual discomfort sensation can be both operationalised and measured, utilising many light-induced physiological measures. These measurements were coupled with visual performance evaluations, in combination with conventional measures of photometric measurements and subjective evaluations. The variables measured were mean Pupil Diameter, Pupillary Unrest Index, Blink Rate, Blink Amplitude, number of fixational eye movements during reading (Fixation Rate), and average Fixation Duration, as well as Combined Visual Performance. The results of this study indicate that most of these parameters show significant differences between high and low lighting conditions. In particular, participants in high discomfort conditions exhibited a higher Fixation Rate, lower Blink Rate, higher Blink Amplitude and a smaller Pupil Diameter than those in both low and medium discomfort conditions. In other words, the studied physiological measures can be used as an index of high levels of glare or visual discomfort. In addition, regarding subjective evaluations, the results of correlation analysis suggest that visual comfort level ratings may provide a more reliable indicator of visual discomfort sensation. Highlights: An experimental study of the effects of lighting conditions on user physiological responses and visual performance. The studied physiological measures can be used as indicators of high levels of glare or visual discomfort. Fixational eye movements were significantly increased in high discomfort conditions. Blink Rate and Amplitude were significantly affected by a high level of discomfort glare.